Until dirt do us apart: On the unremarkable palp morphology of the spider Sternospina concretipalpis Schmidt & Krause, 1993, with comments on the genus Prionolaema Simon, 1894 (Araneae, Tetragnathidae) - Dimitrov, Dimitar; Álvarez-Padilla, Fernando; Hormiga, Gustavo (Zootaxa, 2008)
Examination of the holotype of the tetragnathid spider Sternospina concretipalpis Schmidt & Krause, 1993 demonstrates that the extraordinary claim by the authors of the original description of this species that the male palps are fused is unfounded. The monotypic genus Sternospina Schmidt & Krause, 1993 is a junior synonym of Tylorida Simon, 1894 and S. concretipalpis is a junior synonym of the common species Tylorida striata (Thorell, 1877). The genus Prionolaema Simon, 1894 is a junior synonym of Tetragnatha Latreille, 1804, resulting in two new combinations, Tetragnatha aetherea (Simon, 1894) and T. gracilis (Bryant, 1923). Tetragnatha earmra Levi, 1981 is a junior synonym of Tetragnatha gracilis (Bryant, 1923).